A Themed Issue on Mathematical Inequalities, Analytic Combinatorics and Related Topics in Honor of Professor Feng Qi - Du, Wei-Shih; Agarwal, Ravi; Karapinar, Erdal; Kostić, Marko; Cao, Jian (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The purpose of this Special Issue is to pay tribute to the significant contributions made by Professor Feng Qi in these fields and to provide some important recent advances in theory, methods, and applications.